Managing diversity: reasoning ibn Khaldun's thought in line with the need to build multicultural education - Kurniawan, Syamsul; Maimunah; Nurhaliza, Feni (ATTARBIYAH: Journal of Islamic Culture and Education, 2025)
This research examines the relevance of Ibn Khaldun's thoughts in contemporary multicultural education, particularly in building an inclusive and harmonious multicultural education system. This research argues that the social concepts proposed by Ibn Khaldun, such as ashabiyyah (social solidarity), are fundamental in managing diversity in education. By understanding diversity as a source of strength, education must be able to form social habits that strengthen relationships between different groups and build social solidarity. The method used in this research is a qualitative approach with a literature study type. Research findings show that although multicultural education offers opportunities to shape more inclusive and tolerant individuals, the reality on the ground often presents significant challenges. Diversity in education still causes tensions between different groups, whether religious, ethnic, or social. This study found that applying the principle of ashabiyyah, which emphasizes social solidarity, and using an educational approach based on compassion and gradual repetition of concepts can help overcome these challenges. Additionally, teaching methods emphasizing developing social and emotional skills, such as effective communication and empathy, are highly relevant for creating individuals ready to live harmoniously in a diverse society.